1988
DOI: 10.1093/aepp/10.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Farmers' Hedging Decisions

Abstract: Few farmers use futures markets in spite of theoretical research that says they should and educational efforts to get them to do so. This paper sought to determine the factors that explain why a sample of Indiana farmers use futures markets. Survey results showed that on average futures markets were perceived to both reduce risk and increase income. The most important factors explaining the use of futures markets were the individual's perception of the ability of futures markets to reduce risk and the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
57
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 17 publications
10
57
0
2
Order By: Relevance
“…However, Shapiro and Brorsen (1988) found the opposite. In this regard, the authors suggested that this result is consistent with the human capital theory, where risk aversion decreases with increases in education and experience.…”
Section: Related Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…However, Shapiro and Brorsen (1988) found the opposite. In this regard, the authors suggested that this result is consistent with the human capital theory, where risk aversion decreases with increases in education and experience.…”
Section: Related Studiesmentioning
confidence: 91%
“…These studies are all based on survey data and maximum likelihood econometric estimation and revealed that farmers' preference is a function of their specific socio-economic circumstances. Most of studies established that age, as a proxy for experience, has an insignificant, negative association towards the hedging adoption (Fletcher & Terza, 1986;Asplund et al, 1989;Edelman et al, 1990;Shapiro & Brorsen, 1988;Musser et al, 1996;Katchova & Miranda, 2004). Shapiro and Brorsen (1988), along with Musser et al (1996), suggested that one explanation of this result is that a more experienced farmer has the ability to effectively use the spot market.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse resultado foi similar ao obtido por SHAPIRO & BRORSEN (1988), ASPLUND et al (1989), MAKUS et al (1990, GOODWIN & SCHROEDER (1994), MARQUES & AGUIAR (2004), SILVEIRA et al (2011.…”
Section: Grau De Intensidade Tecnológica (It)unclassified
“…Estudos têm analisado os fatores que levam à adoção de técnicas de gestão do risco de preço na agropecuária (SHAPIRO & BRORSEN, 1988;ASPLUND et al, 1989;MAKUS et al, 1990;TURVEY & BARKER, 1990;GOODWIN & SCHROEDER, 1994;PENNINGS & LEUTHOLD, 2000;VELANDIA et al, 2009;MARQUES & AGUIAR, 2004;SILVEIRA et al, 2011). Estes dois últimos foram desenvolvidos a partir de pesquisas com sojicultores e cafeicultores nacionais, respectivamente.…”
unclassified